2008
DOI: 10.1210/jc.2007-1370
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Weight Loss after Bariatric Surgery for Morbid Obesity on Vascular Endothelial Growth Factor-A, Adipocytokines, and Insulin

Abstract: Serum VEGF-A levels are significantly higher in obese patients than in lean controls, decreasing after weight loss with bariatric surgery, behaving similarly to other hormones related to adipose mass like leptin and insulin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
81
6
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 39 publications
14
81
6
4
Order By: Relevance
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our investigation corroborates preliminary studies (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) as it shows that obesity is a state of chronic low-grade inflammation and the weight reduction resulting from bariatric surgery significantly improves the inflammatory state. This amelioration relies on the continuous reduction in hs-CRP and IL-6 concentrations, associated with a parallel decrease in BMI.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have demonstrated that surgically induced weight loss is accompanied by an improvement of the endothelial function (18,19,21) and the proinflammatory state (18,(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, few studies have studied endothelial function and proinflammatory state together, and have considered different time-points to determine postsurgical changes.…”
Section: Introductionmentioning
confidence: 99%
“…This association was still evident in models with BMI adjustment, pointing to a direct, adiposity-independent effect on insulin action. The protein encoded by VEGFA is known to be involved in adipogenesis, and raised levels of serum VEGFA have previously been shown to be associated with overweight and obesity [17,18]. A German study of 1,578 non-diabetic individuals reported that a variant (rs9472138 T allele) in VEGFA was associated with increased insulin secretion [19].…”
Section: Discussionmentioning
confidence: 99%
“…31 Leptin levels decrease significantly after bariatric surgery in proportion to loss of total body fat. 68 Furthermore, a decrease in leptin after bariatric surgery was inversely correlated with increased levels of markers of bone formation and resorption. The increment in markers of resorption, however, significantly exceeded that of markers of formation indicating a tipping of the balance toward bone loss.…”
Section: Impact Of Bariatric Surgery On Bone Metabolismmentioning
confidence: 97%